Three-dimensional structure fiber composite material and preparation method and application thereof

Through three-dimensional molding and curing molding and subsequent silicon carbide treatment, the problems of uneven distribution of carbon fibers and insufficient mechanical properties in C/C-SiC composites are solved, and the uniformity and high mechanical properties of the material are achieved.

CN119841656APending Publication Date: 2025-04-18BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311345365.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing C/C-SiC composite materials have problems such as uneven distribution of carbon fibers, low compressive strength and bending strength.

Method used

Using the preparation method of three-dimensional structural fiber composite, a mixture containing chopped fibers, resin and carbon powder is subjected to three-dimensional molding and molding, pressure and heating are applied to uniformly cure, and then carbonization and silicon permeation are carried out.

Benefits of technology

The uniform distribution of carbon fiber is achieved, the transverse and longitudinal compressive strength and flexural strength of the material are improved, and the material performance is excellent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841656A_ABST
    Figure CN119841656A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, and discloses a three-dimensional structure fiber composite material and a preparation method and application thereof. Wherein the ratio of the transverse compressive strength to the longitudinal compressive strength of the three-dimensional structure fiber composite material is 0.9-1.3, and the ratio of the transverse compressive strength to the longitudinal bending strength of the three-dimensional structure fiber composite material is 0.9-1.5. According to the mixture disclosed by the invention, pressure and temperature outside a mold can be uniformly transmitted to all directions through a three-dimensional mold pressing curing molding mode, so that the situation that most of fibers are subjected to two-dimensional transverse change due to the fact that traditional mold pressing is only pressed in a single direction in the curing molding process of the fibers and the filler is avoided, and three-dimensional structure carbon fibers formed by uniform pressing are uniformly distributed; the compressive strength and the bending strength are higher, and the material performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a three-dimensional structural fiber composite material and a preparation method and application thereof. Background Art

[0002] C / C-SiC composite material has good anti-oxidation and corrosion resistance, excellent mechanical and thermophysical properties, and is a high-temperature structural functional material. The preparation processes of C / C-SiC composite materials include chemical vapor infiltration, precursor conversion and melt siliconization. The current process has the disadvantages of low carbon deposition efficiency, easy surface crusting, long production cycle and high process cost.

[0003] CN108658613 discloses a method for preparing automobile brake discs by fiber molding, wherein short carbon fibers and resin are mixed to obtain prepreg, and a step-pressurization and step-temperature unidirectional molding process is used. After cooling and demolding, a carbon fiber reinforced resin-based composite material is obtained, and then high-temperature carbonization is performed to obtain a porous carbon-based composite material. Finally, molten silicon penetrates into the interior of the composite material through capillary action to form a silicon carbide ceramic matrix with high density and strength.

[0004] However, the existing C / C-SiC composite materials have problems such as uneven carbon fiber distribution, low compressive strength and flexural strength. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of uneven carbon fiber distribution, low compressive strength and flexural strength of C / C-SiC composite materials in the prior art, and to provide a three-dimensional structural fiber composite material and its preparation method and application.

[0006] In order to achieve the above objectives, the first aspect of the present invention provides a three-dimensional structural fiber composite material, wherein the ratio of the transverse compressive strength to the longitudinal compressive strength of the three-dimensional structural fiber composite material is 0.9-1.3, and the ratio of the transverse compressive strength to the longitudinal bending strength is 0.9-1.5.

[0007] A second aspect of the present invention provides a method for preparing a three-dimensional structural fiber composite material, comprising:

[0008] (1) molding a mixture containing chopped fibers, resin, and carbon powder, wherein during the molding process, pressure is applied to the mixture in three-dimensional directions to obtain a preform;

[0009] (2) carbonizing the preform to obtain a preform;

[0010] (3) The preform is siliconized to obtain the three-dimensional structural fiber composite material.

[0011] The third aspect of the present invention provides a three-dimensional structural fiber composite material obtained by the preparation method.

[0012] A fourth aspect of the present invention provides application of the three-dimensional structural fiber composite material in the braking field.

[0013] Through the above technical scheme, the mixture of the present invention can be cured by three-dimensional molding to evenly transfer the pressure and temperature outside the mold to all directions, so that during the curing and molding process of the fibers and fillers, most of the fibers will not undergo two-dimensional lateral changes due to the traditional molding process where only one direction of pressure is applied. The three-dimensional structure formed by uniform pressure has uniform carbon fiber distribution, high compressive strength and bending strength, and excellent material properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Schematic diagram of the molding of three-dimensional structural fiber composite materials.

[0015] Reference numerals

[0016] 1: X direction; 2: Z direction; 3: Y direction. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] A first aspect of the present invention provides a three-dimensional structural fiber composite material, wherein the ratio of the transverse compressive strength to the longitudinal compressive strength of the three-dimensional structural fiber composite material is 0.9-1.3, and the ratio of the transverse compressive strength to the longitudinal bending strength is 0.9-1.5.

[0019] In some specific embodiments of the present invention, preferably, the ratio of the transverse compressive strength to the longitudinal compressive strength of the three-dimensional structural fiber composite material is 0.98-1.05, and the ratio of the transverse compressive strength to the longitudinal flexural strength is 0.98-1.05.

[0020] The three-dimensional structural fiber composite material obtained by the present invention is formed by subjecting a mixture containing chopped fibers, resin and carbon powder to a three-dimensional compression curing molding method. The three-dimensional compression curing molding method can evenly transmit the pressure and temperature outside the mold to all directions, and the three-dimensional structural carbon fibers formed by uniform pressure are evenly distributed, the transverse and longitudinal compressive strengths are basically the same, and the transverse and longitudinal bending strengths are basically the same, indicating that the carbon fibers of the material are evenly distributed, the compressive strength and bending strength are high, and the material performance is excellent.

[0021] In some specific embodiments of the present invention, the compressive strength of the three-dimensional structural fiber composite material is 290-410 MPa, and the flexural strength is 130-190 MPa. The three-dimensional structural fiber composite material obtained by the present invention has high mechanical strength and excellent material properties.

[0022] In some specific embodiments of the present invention, the three-dimensional structural fiber composite material includes: carbon fiber, silicon carbide and free silicon.

[0023] A second aspect of the present invention provides a method for preparing a three-dimensional structural fiber composite material, comprising:

[0024] (1) molding a mixture containing chopped fibers, resin, and carbon powder, wherein during the molding process, pressure is applied to the mixture in three-dimensional directions to obtain a preform;

[0025] (2) carbonizing the preform to obtain a preform;

[0026] (3) The preform is siliconized to obtain the three-dimensional structural fiber composite material.

[0027] In some specific embodiments of the present invention, the three-dimensional structural fiber composite material has fibers distributed in the XYZ directions, and the distribution is uniform, with each direction accounting for about 33.3%±5%. The XYZ directions refer to three mutually perpendicular directions in a three-dimensional rectangular coordinate system. Generally, the Z direction is a direction perpendicular to the ground, and the X and Y directions are two mutually perpendicular directions parallel to the ground. The mixture of the present invention can be formed by three-dimensional molding and curing to form a uniform pressure and temperature outside the mold in all directions, so that during the curing and forming process of the fibers and fillers, most of the fibers will not change in two-dimensional lateral direction due to the traditional molding that only compresses in one direction. The three-dimensional structural carbon fibers formed by uniform compression are evenly distributed, and the transverse and longitudinal compressive strengths are basically the same, and the transverse and longitudinal bending strengths are basically the same, indicating that the carbon fiber distribution of the material is uniform, the compressive strength and bending strength are high, and the material performance is excellent.

[0028] In some specific embodiments of the present invention, Figure 1As shown, during the molding process, the mixture is heated to a first temperature and then pressure is applied in the Z direction, and the compression amount is 25-50% of the mold length, wherein the compression amount is the percentage change of the mold length obtained by compression in a specific direction compared to the mold length before compression; the obtained material is then heated to a second temperature, and then a pressure of 5-8MPa is applied in the X direction, and the Z direction is perpendicular to the X / Y direction. By controlling the compression amount within the above range, the composite material can be uniformly compressed, and the obtained three-dimensional structural fiber composite material has high compressive strength and flexural strength, and excellent material properties. The Z direction described in the present invention is relative to the X / Y direction. Figure 1 As described above, the vertical direction is set as the Z direction, and its corresponding vertical plane is the X / Y direction, while the horizontal direction is set as the Z direction, and its corresponding vertical plane is the X / Y direction.

[0029] In some specific embodiments of the present invention, in step (1), the first temperature is 90-110° C. The first temperature allows the embryo to have a certain fluidity and pre-press, at which time some fibers are on the XY plane. Within the temperature range, the resin has good fluidity, which can effectively improve the strength and performance of the material.

[0030] In some specific embodiments of the present invention, in step (1), the pressure applied in the Z direction is 2-3 MPa, and the pressure application time is 10-30 min. The pressure is applied in the Z direction for a pre-compression, so that the fibers can be distributed in the XY direction. Within the pressure range, the density of the mixture is better, and the three-dimensional structure formed by uniform pressure can effectively improve the strength and performance of the material. When the pressure in the Z direction is increased, when the pressure applied in the Z direction is too large, the pressure is too dense, and when the force is applied in the X direction, the compression amount will be insufficient, and the fiber movement will be insufficient.

[0031] In some specific embodiments of the present invention, in step (1), the second temperature is 150-180°C, and the fluidity is best within the second temperature range, so that the fibers not on the XY plane are pressed onto other planes to form a three-dimensional structure. Within the temperature range, the resin has good fluidity, which can effectively improve the strength and performance of the material.

[0032] In some specific embodiments of the present invention, in step (1), the pressure applied in the X direction is 5-8MPa, and the pressure application time is 1.5-2.5h. When the pressure is applied in the X direction, the embryo has a certain density, and the pressure needs to be increased to obtain a sufficient amount of compression. Within the pressure range, the density of the mixture is better, and the three-dimensional structure formed by uniform pressure can effectively improve the strength and performance of the material. When the pressure is insufficient, the embryo will not be compacted and the overall bonding strength will be low.

[0033] In the present invention, under the combined action of the first temperature and the second temperature and under applied pressure, the resin has good fluidity, and the composite material can be evenly compressed. At the same time, the uniform compression can effectively improve the strength and performance of the material. The obtained three-dimensional structural fiber composite material has high compressive strength and flexural strength, and the material performance is excellent.

[0034] In some specific embodiments of the present invention, before obtaining the mixture, the chopped fibers are heat treated to change the fiber surface and enhance the bonding force between the fibers and the resin; wherein the heat treatment temperature is 400-800°C and the heat treatment time is 2-5h.

[0035] In some specific embodiments of the present invention, the length of the chopped fibers is 5-40 mm, and the chopped fibers within this length range can improve the uniformity of the mixture. If the fibers are too short, the pressing will be too dense, affecting siliconization and reducing performance. If the fibers are too long, the pressing density is insufficient and the performance will be reduced.

[0036] In some specific embodiments of the present invention, the resin is selected from one or more of phenolic resin, furfural resin and furan resin with a residual carbon content of 40-60wt%. The phenolic resin has a residual carbon content of 40-60wt%, which can adhere to the surface of carbon fiber to protect the carbon fiber and increase the density of the embryo.

[0037] In some specific embodiments of the present invention, the filler is the sum of resin and carbon powder, and the mass ratio of the chopped fibers to the filler is 30-60:40-70. The three-dimensional structural fiber composite material within this mass ratio has better flexural strength.

[0038] In some specific embodiments of the present invention, the mass ratio of the resin to the carbon powder is 80-60:20-40.

[0039] In some specific embodiments of the present invention, in step (2), the carbonization temperature is 800-1200° C., and the carbonization time is 15-48 hours.

[0040] In some specific embodiments of the present invention, the siliconizing process includes: filling silicon powder, placing a support, and placing the preform.

[0041] In some specific embodiments of the present invention, the siliconizing conditions include: the vacuum degree reaches 10 -3 -10 -1 Pa, the siliconizing temperature is 1500-1700°C, and the siliconizing time is 2-5h.

[0042] The third aspect of the present invention provides a three-dimensional structural fiber composite material obtained by the preparation method.

[0043] The composite material has uniform distribution of carbon fibers, high compressive strength and flexural strength, as described above, and will not be repeated here. The ratio of the transverse compressive strength to the longitudinal compressive strength and the ratio of the transverse compressive strength to the longitudinal flexural strength of the composite material can show the uniformity of the material. The closer the ratio of the transverse compressive strength to the longitudinal compressive strength and the ratio of the transverse compressive strength to the longitudinal flexural strength are to 1, the better the uniformity of the composite material and the more uniform the distribution of the carbon fibers.

[0044] The fourth aspect of the present invention provides the application of the three-dimensional structural fiber composite material in the field of braking, wherein the braking field can be a brake disc material or other braking materials.

[0045] The present invention will be described in detail below through examples.

[0046] Test method:

[0047] Compressive strength: First, fix the sample on the testing machine, and then apply a pressure perpendicular to the sample surface to record the pressure at failure; P = F / A; where P is the compressive strength, F is the maximum test pressure, and A represents the pressure-bearing area of ​​the cubic test block.

[0048] Bending strength: Four-point bending test method (1) Prepare a rectangular specimen of standard size; (2) Place the specimen between four supporting points. The distance between the supporting points is called the support distance; (3) Apply a downward force between the two supporting points of the specimen to cause the specimen to bend; (4) Measure the length change or displacement of the specimen before and after bending, and record the applied force; (5) Calculate the bending strength of the specimen based on the measured data.

[0049] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.

[0050] Example 1

[0051] (1) Chopped fibers with a length of 10 mm were selected, heat treated at 800° C. for 3 h, and uniformly mixed with a high carbon residue phenolic resin with a carbon residue value of 50% and carbon powder to obtain a mixture, wherein the mass ratio of the chopped fibers to the filler was 30:70, and the mass ratio of the resin to the carbon powder was 80:20.

[0052] (2) Fill the mixture into a square prefabricated brake disc mold coated with a release agent, and place it in a molding machine for molding after the mold is closed. Heat the molding machine to 110°C, at which time the filler has slight fluidity. Apply pressure in the Z direction at a pressure of 3MPa, and the compression amount is 25-27% of the mold length. The pressure is applied for 20 minutes; then heat the molding machine to 150°C, at which time the filler has the best fluidity. Apply pressure in the X direction at a pressure of 8MPa. A small amount of 45° and a large amount of 0° fibers in the molding machine will be partially compressed to 90°, and the pressure is applied for 2.5 hours. After molding and thermosetting, the mold is naturally cooled to room temperature and demolded to obtain a preform.

[0053] (3) The preform is carbonized at a carbonization temperature of 1000° C. for 30 h to obtain a preform.

[0054] (4) The preform is siliconized at a vacuum degree of 10 -2 Under Pa conditions, the siliconizing temperature was 1600°C and the siliconizing time was 3h, and a three-dimensional structural fiber composite material was obtained, which was recorded as A1.

[0055] Example 2

[0056] (1) Chopped fibers with a length of 10 mm were selected and heat-treated at 800° C. for 3 h. The fibers were uniformly mixed with a high carbon residue phenolic resin with a carbon residue value of 50% and carbon powder to obtain a mixture. The mass ratio of the chopped fibers to the filler was 40:60, and the mass ratio of the resin to the carbon powder was 80:20.

[0057] (2) Fill the mixture into a square prefabricated brake disc mold coated with a release agent, and place it in a molding machine for molding after the mold is closed. Heat the molding machine to 110°C, at which time the filler has slight fluidity. Apply pressure in the Z direction at a pressure of 3MPa, and the compression amount is 30-32% of the mold length. The pressure application time is 20min; then heat the molding machine to 150°C, at which time the filler has the best fluidity. Apply pressure in the X direction at a pressure of 8MPa. A small amount of 45° and a large amount of 0° fibers in the molding machine will be partially compressed to 90°. The pressure application time is 2.5h. After molding and thermosetting, the mold is naturally cooled to room temperature for demolding to obtain a preform.

[0058] (3) The preform is carbonized at a carbonization temperature of 1000° C. for 30 h to obtain a preform.

[0059] (4) The preform is siliconized at a vacuum degree of 10 -2 Under Pa conditions, the siliconizing temperature was 1600°C and the siliconizing time was 3 h, and a three-dimensional structural fiber composite material was obtained, which was recorded as A2.

[0060] Example 3

[0061] (1) Chopped fibers with a length of 10 mm were selected and heat-treated at 800° C. for 3 h. The fibers were uniformly mixed with a high carbon residue phenolic resin with a carbon residue value of 50% and carbon powder to obtain a mixture. The mass ratio of the chopped fibers to the filler was 50:50, and the mass ratio of the resin to the carbon powder was 80:20.

[0062] (2) Fill the mixture into a square prefabricated brake disc mold coated with a release agent, and place it in a molding machine for molding after the mold is closed. Heat the molding machine to 110°C, at which time the filler has slight fluidity. Apply pressure in the Z direction at a pressure of 3MPa, and the compression amount is 36-39% of the mold length. The pressure application time is 20min; then heat the molding machine to 150°C, at which time the filler has the best fluidity. Apply pressure in the X direction at a pressure of 8MPa. A small amount of 45° and a large amount of 0° fibers in the molding machine will be partially compressed to 90°. The pressure application time is 2.5h. After molding and thermosetting, the mold is naturally cooled to room temperature and demolded to obtain a preform.

[0063] (3) The preform is carbonized at a carbonization temperature of 1000° C. for 30 h to obtain a preform.

[0064] (4) The preform is siliconized at a vacuum degree of 10 -2 Under Pa conditions, the siliconizing temperature was 1600℃ and the siliconizing time was 3h, and a three-dimensional structural fiber composite material was obtained, which was recorded as A3.

[0065] Example 4

[0066] (1) Chopped fibers with a length of 10 mm were selected, heat treated at 800° C. for 3 h, and uniformly mixed with a high carbon residue phenolic resin with a carbon residue value of 50% and carbon powder to obtain a mixture, wherein the mass ratio of the chopped fibers to the filler was 60:40, and the mass ratio of the resin to the carbon powder was 80:20.

[0067] (2) Fill the mixture into a square prefabricated brake disc mold coated with a release agent, and place it in a molding machine for molding after the mold is closed. Heat the molding machine to 110°C, at which time the filler has slight fluidity. Apply pressure in the Z direction at a pressure of 3MPa, and the compression amount is 48-50% of the mold length. The pressure application time is 20min; then heat the molding machine to 150°C, at which time the filler has the best fluidity. Apply pressure in the X direction at a pressure of 8MPa. A small amount of 45° and a large amount of 0° fibers in the molding machine will be partially compressed to 90°. The pressure application time is 2.5h. After molding and thermosetting, the mold is naturally cooled to room temperature and demolded to obtain a preform.

[0068] (3) The preform is carbonized at a carbonization temperature of 1000° C. for 30 h to obtain a preform.

[0069] (4) The preform is siliconized at a vacuum degree of 10 -2 Under Pa conditions, the siliconizing temperature was 1600°C and the siliconizing time was 3 h, and a three-dimensional structural fiber composite material was obtained, which was recorded as A4.

[0070] Example 5

[0071] (1) Chopped fibers with a length of 10 mm were selected, heat treated at 800° C. for 3 h, and uniformly mixed with a high carbon residue phenolic resin with a carbon residue value of 50% and carbon powder to obtain a mixture, wherein the mass ratio of the chopped fibers to the filler was 30:70, and the mass ratio of the resin to the carbon powder was 60:40.

[0072] (2) Fill the mixture into a square prefabricated brake disc mold coated with a release agent, and place it in a molding machine for molding after the mold is closed. Heat the molding machine to 110°C, at which time the filler has slight fluidity. Apply pressure in the Z direction at a pressure of 3MPa, and the compression amount is 25-27% of the mold length. The pressure is applied for 20 minutes; then heat the molding machine to 150°C, at which time the filler has the best fluidity. Apply pressure in the X direction at a pressure of 8MPa. A small amount of 45° and a large amount of 0° fibers in the molding machine will be partially compressed to 90°, and the pressure is applied for 2.5 hours. After molding and thermosetting, the mold is naturally cooled to room temperature and demolded to obtain a preform.

[0073] (3) The preform is carbonized at a carbonization temperature of 1000° C. for 30 h to obtain a preform.

[0074] (4) The preform is siliconized at a vacuum degree of 10 -2 Under Pa conditions, the siliconizing temperature was 1600℃ and the siliconizing time was 3h, and a three-dimensional structural fiber composite material was obtained, which was recorded as A5.

[0075] Example 6

[0076] The same as Example 1, except that in step (1), short-cut fibers with a length of 3 mm are selected.

[0077] Example 7

[0078] The same as Example 1, except that in step (1), short-cut fibers with a length of 45 mm are selected.

[0079] Example 8

[0080] The same as Example 1, except that in step (2), a pressure of 4 MPa is applied in the X direction.

[0081] Example 9

[0082] The method is the same as Example 1, except that in step (2), a pressure of 20 MPa is applied in the X direction.

[0083] Example 10

[0084] The same as Example 1, except that in step (2), a pressure of 5 MPa is applied in the Z direction, the compression amount is 30-32% of the mold length, and the pressure application time is 20 min.

[0085] Comparative Example 1

[0086] (1) Chopped fibers with a length of 10 mm were selected, heat-treated at 800° C. for 3 h, and uniformly mixed with high-residual-carbon phenolic resin, furfural resin, or furan resin and carbon powder to obtain a mixture, wherein the mass ratio of the chopped fibers to the filler was 30:70, and the mass ratio of the resin to the carbon powder was 80:20.

[0087] (2) Fill the mixed material into a square prefabricated brake disc mold coated with a release agent, and place it in a molding machine for molding after the mold is closed. Heat the molding machine to 150°C, at which time the filler has the best fluidity, apply pressure in the Z direction, the pressure is 8MPa, the compression amount is 25-27% of the mold length, and the pressure application time is 2.5h. After molding and thermosetting, the mold is naturally cooled to room temperature and demolded to obtain a prefabricated part.

[0088] (3) The preform is carbonized at a carbonization temperature of 1000° C. and a carbonization time of 30 h to obtain a preform.

[0089] (4) The preform is siliconized at a vacuum degree of 10 -2 Under Pa conditions, the siliconizing temperature was 1600℃ and the siliconizing time was 3h, and a three-dimensional structural fiber composite material was obtained, which was recorded as D1.

[0090] The main performance tests of the composite materials are carried out and the results are shown in Table 1.

[0091] Table 1

[0092]

[0093]

[0094] It can be seen from the results in Table 1 that the embodiments 1-4 of the present invention have significantly better bending and compression resistance. It can be seen from the embodiments 1-4 and the comparative example 1 that when the X-direction pressure is increased, the bending and compression transverse and longitudinal test performances have little difference and better uniformity.

[0095] Embodiments 1-4 adjust the compression amount by adjusting the ratio of fiber mixed fillers, and then adjust the distribution ratio in the direction of compressed fibers. The amount of chopped fibers in Embodiment 1 is higher than that in Embodiments 2-4, and both the compressive strength and the flexural strength are higher than those in Embodiments 2-4, indicating that as the amount of fibers increases and the amount of silicon carbide decreases, the compressive strength and the flexural strength decrease.

[0096] It can be seen from Example 1 and Examples 6-7 that if the fiber is too short, the pressing will be too dense, which will affect siliconization and reduce performance; if the fiber is too long, the pressing density is insufficient and the performance will reduce.

[0097] It can be seen from Example 1 and Examples 8-9 that when the pressure applied in the X direction is 5-8 MPa, the mixture has better compactness, and the three-dimensional structure formed by uniform pressure can effectively improve the strength and performance of the material. When the pressure is lower or higher than the above range, the overall performance of the composite material decreases.

[0098] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A three-dimensional structural fiber composite material, characterized in that: The ratio of the transverse compressive strength to the longitudinal compressive strength of the three-dimensional structural fiber composite material is 0.9-1.3, and the ratio of the transverse compressive strength to the longitudinal bending strength is 0.9-1.

5.

2. The three-dimensional structural fiber composite material according to claim 1, wherein: The ratio of the transverse compressive strength to the longitudinal compressive strength of the three-dimensional structural fiber composite material is 0.98-1.05, and the ratio of the transverse compressive strength to the longitudinal bending strength is 0.98-1.05; Preferably, the three-dimensional structural fiber composite material has a compressive strength of 290-410 MPa and a flexural strength of 130-190 MPa.

3. A method for preparing a three-dimensional structural fiber composite material, characterized in that: include: (1) molding a mixture containing chopped fibers, resin, and carbon powder, wherein during the molding process, pressure is applied to the mixture in three-dimensional directions to obtain a preform; (2) carbonizing the preform to obtain a preform; (3) The preform is siliconized to obtain the three-dimensional structural fiber composite material.

4. The preparation method according to claim 3, characterized in that: During the molding process, the mixed material is heated to a first temperature and then pressure is applied in the Z direction, with a compression amount of 25-50% of the mold length; then the obtained material is heated to a second temperature, and a pressure of 5-8 MPa is applied in the X direction, wherein the Z direction is perpendicular to the X / Y direction.

5. The preparation method according to claim 3 or 4, characterized in that: In step (1), the first temperature is 90-110°C.

6. The preparation method according to claim 4 or 5, characterized in that: In step (1), the pressure applied in the Z direction is 2-3 MPa, and the pressure application time is 10-30 minutes.

7. The preparation method according to any one of claims 4 to 6, characterized in that: In step (1), the second temperature is 150-180°C.

8. The preparation method according to any one of claims 4 to 7, characterized in that: In step (1), the pressure applied in the X direction is 5-8 MPa, and the pressure application time is 1.5-2.5 hours.

9. The preparation method according to any one of claims 3 to 8, characterized in that: Before obtaining the mixed material, the chopped fibers are heat treated; Preferably, the temperature of the heat treatment is 400-800°C, and the time of the heat treatment is 2-5h; Preferably, the length of the chopped fibers is 5-40 mm; Preferably, the resin is selected from one or more of phenolic resin, furfural resin and furan resin with a residual carbon content of 40-60wt%; Preferably, the filler is the sum of resin and carbon powder, and the mass ratio of the chopped fibers to the filler is 30-60:40-70; Preferably, the mass ratio of the resin to the carbon powder is 80-60:20-40.

10. The preparation method according to any one of claims 3 to 9, characterized in that: In step (2), the carbonization temperature is 800-1200° C., and the carbonization time is 15-48 hours; Preferably, the siliconizing conditions include: the vacuum degree reaches 10 -3 -10 -1 Pa, the siliconizing temperature is 1500-1700°C, and the siliconizing time is 2-5h.

11. The three-dimensional structural fiber composite material obtained by the preparation method according to any one of claims 3 to 10.

12. Use of the three-dimensional structural fiber composite material according to any one of claims 1 to 3 and 11 in the field of braking.